MEMAHAMI TIDAK SYAR’INYA BANK SYARIAH - Ja'far Nasution (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2015)
Islamic banking is finansial institutions are functioning as anintermediary for the excess funds. For those who lack the funds forbusiness activities and other activities in accordance with islamic law.Pioneering Islamic banking system that is else where known as Islamicbanking and booming in this country more than half century the meaningrun in Pakistan Islamic bank in fund management in an innovativepilgrimage. The next development occured in Egypt with the estbishmentof village banks Mit Ghamr this is first Islamic bank the world.Weaknesses and operational experiences to existing Islamic bankincluding Islamic banks have not solicit customers in rural areas.The detailed criticism of Islamic banks area as follows: First, engage inusury muamalat. Second, involved in insurance.third, was neverannounced losses. The fourth, weakness of supervision an management.The five, Aktivis through murabahah is domonant. Six, Lack of skilledhuman resources to manage Islamic financial.With the criticism of Islamic banks can be concluded filled withthings that are doubtful due to various irrequarities sharia in manyaspects.